UTILIZATION OF SOCIAL MEDIA TO FACILITATE STUDENT LEARNING INDEPENDENCE AND CREATIVITY - Muhammad Ihsaan Fathoni; Asri Budiningsih; Suyantiningsih (Journal International of Lingua and Technology, 2025)
Students are individuals who need independent learning and creativity to develop their potential to the maximum. There is a need for learning in the current digital and globalization era, that the use of social media is important for students. Social media is a means of communication and social interaction in cyberspace which can be an effective means of facilitating student learning independence and creativity. One of the advantages of social media is its ability to connect people from different backgrounds and geographies, making it easier for students to interact and share information with their peers. This year's research is a needs assessment of the development of learning models using social media in facilitating student learning independence and creativity. This type of research is descriptive quantitative and qualitative which is carried out in study programs in the FIPP UNY environment. The population is all FIPP UNY students in all S1 study programs and all batches totaling 5253 people. The research sample taken was 372 people. The research instrument used a questionnaire and interview sheet The research results show that: 1). The type of social media that is widely used by FIPP UNY students to facilitate their learning is YouTube 2). The level of use of social media by FIPP UNY students to facilitate their learning is quite high. The majority of students tend to see social media as a useful tool in supporting their learning process 3). The social media that is widely used by FIPP UNY students to facilitate independent learning is YouTube 4). Social media is widely used by FIPP UNY students to increase creativity Youtube 5). FIPP UNY students' obstacles to social media to facilitate learning are related to technical problems, information distortion, security privacy and usage interference.